PERHITUNGAN TITIK IMPAS DENGAN METODE MARGIN KONTRIBUSI SEBAGAI ALAT PERENCANAAN LABA - Syarifudin, Akhmad (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2014)
Calculation of break even or recoup their calculation or computation known as the break-even point is one financial calculation that is very important in financial planning firm. Break Even Point (BEP) can be defined as a point or state where the company in its operations do not benefit and not suffer a loss. In other words, the state of the gain or loss equal to zero.  Contribution margin is the difference between the sales value of the variable costs. Contribution margin can be used to cover the fixed costs, and when they left the rest is profit. If management wants to know the breakeven sales quantity, the amount of the total contribution margin should be equal to the total amount of fixed costs. Small and Medium Enterprises (SMEs) "Pandan Kuning" is a manufacturing company engaged in the production of the production in the form of souvenirs. These SMEs are mass produced souvenirs and orders from customers in both the large and small parties. Therefore the company requires the calculation of the breakeven point in order to produce accounting information that is useful for the planning of short-term profit. Keywords: break-even point, fixed costs, variable costs, contribution margin.